Effect of Nb as dopant of hydrotalcite catalysts during the ethanol condensation to optimize n-Butanol production - Valdivieso-Vera, Daniel Alejandro; Flores-Escamilla, Gerardo Antonio; Cano-Gómez, José Julián; Barroso-Martín, Isabel; Rodríguez-Castellón, Enrique; Santos-López, Iván Alonso; Guerrero-Pérez, María Olga (Elsevier, 2024)
The present study optimizes Cu-supported catalysts on hydrotalcite for the synthesis of n-butanol whose interest is in its use as biofuel, due to its superior performance in comparison with other short-chain alcohols. The catalytic performance was improved by adding Nb to the catalytic formulation. In this way, several Cu-Nb catalysts supported on hydrotalcites (Mg/Al) with different Nb loadings were synthesized by incipient wetness impregnation and characterized by H2 temperature-programmed reduction, X-ray diffraction, N2 physisorption, CO2 and NH3 thermo-programmed desorption and X-ray photoelectron spectroscopy. It was shown that the incorporation of Nb promoted a suitable balance between the acid-basic and redox sites, modulating the Cu0/Cu+ dehydrogenation/hydrogenation properties for the n-BuOH production. The synthesis of multiple value-added products (n-BuOH, acetaldehyde, ethyl acetate, and 1-hexanol) was achieved in both the liquid (at 180 ºC) and gas phase (150 350 ºC), where it was demonstrated that both the n-BuOH selectivity and ethanol con- version improved with the Nb addition. The performance of the catalysts under time on stream and their recycling is also described.
Keywords: Catálisis; Catalizadores; Bioethanol; n-Butanol; Copper; Niobium; Hydrotalcite; Guerbet reaction